BGE 109 IV 161 - Bundesgericht (BGE) (1983)
Regeste Art. 139 Ziff. 2 StGB; qualifizierter Raub. Begriff der "besonderen Gefährlichkeit" in den Art. 139 Ziff. 2 Abs. 4 aStGB und Art. 139 Ziff. 2 Abs. 3 nStGB.